2015
DOI: 10.1002/chem.201500173
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Template‐Directed [2+2] Photocycloadditions of Isoquinolones: Scope, Mechanism and Synthetic Applications

Abstract: A strategy for the enantioselective [2+2] photocycloaddition of isoquinolones with alkenes is presented, in which the formation of a supramolecular complex between a chiral template and the substrate ensures high enantioface differentiation by shielding one face of the substrate. Fifteen different electron-deficient alkenes and ten different substituted isoquinolones undergo efficient photocycloaddition, yielding the cyclobutane products in excellent yields and with outstanding regio-, diastereo- and enantiose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 68 publications
(17 reference statements)
0
13
0
Order By: Relevance
“… Also, the Lewis acid-catalyzed reaction of allene 7 and pinacol ester 8 resulted in cyclobutyl boronate 9 . An example of the photochemical [2 + 2] cycloaddition of vinyl boronate 1 was described for the case of isoquinolone 10 as the cycloaddition partner: the reaction was performed in the presence of a chiral hydrogen-bonding template 11 and led to cyclobutyl boronate derivative 12 . , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… Also, the Lewis acid-catalyzed reaction of allene 7 and pinacol ester 8 resulted in cyclobutyl boronate 9 . An example of the photochemical [2 + 2] cycloaddition of vinyl boronate 1 was described for the case of isoquinolone 10 as the cycloaddition partner: the reaction was performed in the presence of a chiral hydrogen-bonding template 11 and led to cyclobutyl boronate derivative 12 . , …”
Section: Introductionmentioning
confidence: 99%
“…67 An example of the photochemical [2 + 2] cycloaddition of vinyl boronate 1 was described for the case of isoquinolone 10 as the cycloaddition partner: the reaction was performed in the presence of a chiral hydrogenbonding template 11 and led to cyclobutyl boronate derivative 12. 68,69 In this work, we have envisaged the photochemical [2 + 2] cycloaddition of alkenyl boronic derivatives and maleimides as a general method for the synthesis of borylated 3azabicyclo[3.2.0]heptanes. As this methodology for constructing cyclobutane-derived boronates is very scarcely represented in the literature, a wide range of alkenyl boronic derivatives (including those bearing protected amino, ketone, or carboxylate groups) as well as other reaction partners (maleimides and other electron-poor alkenes) have to be studied in the [2 + 2] cycloaddition to evaluate the scope and limitations of the method, keeping in mind the possibility of the multigram synthesis (Scheme 2).…”
Section: ■ Introductionmentioning
confidence: 99%
“…With this in mind, other substrates which contain a lactam binding motif and which show a high intermolecular reaction rate should be equally suitable for the enantioselectively catalyzed intermolecular [2 + 2] photocycloaddition reaction. A preliminary experiment with parent 1­(2 H )-isoquinolone and methyl vinyl ketone revealed that a high enantioselectivity can be achieved also with isoquinolone substrates (Scheme ). Product 8 was obtained as a single isomer in 91% ee .…”
mentioning
confidence: 99%
“…One reason for this discrepancy may be the unique challenge of controlling crossed vs homodimerization in [2 + 2] cycloadditions, thus leading to difficulties in the preparation of many cyclobutanecontaining natural products and similarly complex bioactive cyclobutane compounds. [90] Yoon et al report a conceptually novel approach for chiral Lewis acid catalyzed crossed [2 + 2] photocycloaddition for the synthesis of a series of vinylcyclobutanes with high enantioselectivity. [91] In 2017, they reported a Sc(OTf) 3 catalyzed chalcones (Scheme 20), [92] which enabled the highly enantioselective crossed [2 + 2] cycloaddition of styrenic olefins and provided a controlled method to directly synthesize 1,2-diarylcyclobutane structures.…”
Section: Combining Lewis Acid Catalysis With Photoredox Catalysismentioning
confidence: 99%